Breaking the Cycle: Public Policy Innovations for Disability Inclusion and Poverty Reduction in Indonesia - Hajad, Vellayati; Ikhsan, Ikhsan; Herizal, Herizal; Latif, Ikhwan Rahmatika; Saputra, Ilham Mirza (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2025)
This study explores innovative public policy strategies to break the cycle of disability-related poverty in Indonesia through a comprehensive literature review. The analysis reveals that barriers to education, employment, health services, and social protection, exacerbated by discrimination and stigma, are structural and mutually reinforcing poverty and exclusion. Grounded in the social model of disability and the capability approach, the study emphasizes that poverty is not merely a result of impairment but systemic obstacles limiting individual agency and opportunity. It highlights the role of Law Number 8 of 2016 as a foundational legal framework while stressing the need for consistent implementation, cross-sectoral coordination, and active participation of persons with disabilities in policymaking. Promising approaches include inclusive governance, accessible infrastructure, skills development programs, and stigma reduction initiatives. The study contributes theoretically by reinforcing the view that disability inclusion is a matter of rights and a strategic imperative for sustainable development and social justice. Embedding inclusive values into the core of public policy is key to reducing inequality and ensuring no one is left behind in Indonesia’s development.